PERMAINAN KOLASE UNTUK MENINGKATKAN MOTORIK HALUS PADA KELOMPOK A TK MUSLIMAT NU BANJARMASIN - Huda, Huda; Faeruz, Ratna; Hayati, Miratul (Journal of Early Childhood Education (JECE), 2019)
The purpose of this study was to improve children’s fine motor skills through collage play in groip A at Muslimat NU Banjarmasin Kindegarten. This research is collaborative classroom action research using Kemmis and Mc Taggart model. The subjects of the study are 10 children in group A at Muslimat NU Kindergarten. The object of this study is the children’s fine motor skill. Guided observation is used for this instrument. The data analysis technique is carried out qualitatively and quantitatively. This research was conducted in two cycles. The result shows a gradual increase in children’s fine motor skills. Improvement of children’s fine motor skill through collage play in the implementation of pre-liminary research 40,45% and in the first cycle increased to 50,59%. In 2nd cycle, the child’s fine motor ability increased with percentage 80,68%.